Uso de Suplementos Nutricionales Orales en el Paciente con Enfermedad Renal Crónica en Diálisis y Prediálisis - Arley Vargas, Diego Armando (2020)
Energy protein wasting is a clinical syndrome with important implications in patients with chronic kidney disease, increasing mortality morbidity;  Supplementation with nutritional formulas improves the nutritional status of patients with chronic kidney disease in dialysis and predialysis.